Validation of distributed energy resources in accordance with voltage fluctuation limitations prescribed by the IEEE 1547-2018 standard - Dimitrijević, Marko A. (JET on-line, 2023)
The increased need for clean energy and global warming is among the biggest challenges of the modern age. One of the potential solutions to these challenges, which can be achieved by using existing technologies, are distributed energy resources (DER). DER can be an isolated system of different capacity and purpose, but, in most cases, it is connected to the electricity grid. Connecting a DER system to the electricity grid is a complex task, the complexity in-creases with the number of integrated DERs. In order to regulate interoperability and interconnection of DERs with electricity grid, the IEEE 1547-2018 standard is imposed. Among other requirements, the standard prescribes voltage fluctuation limitations induced by the DER. The analysis of voltage fluctuations – flicker assumes measurement procedures defined by IEEE 1453-2015 standard and implementation of digital flicker-meter described by IEC 61000- 4-15 standard. In this proceeding, the realization of virtual instrument for voltage fluctuation analysis will be presented. This function is part of more comprehensive system for DER validation.
Keywords: distributed energy resources; flicker; nihanja napetosti; porazdeljeni viri energije; utripanje; voltage fluctuations